Research on the Properties of Rights Related to Online Accounts - Zeyu Zheng (Studies in Law and Justice, 2023)
Account-based virtual property (or “network account”) is a new type of property born in the digital age. By registering, users sign a service contract with an operator to obtain an exclusive account. Regarding the properties of their related rights, our laws are not clear, so they are prone to legal disputes. It was found that these rights are claims arising from service contracts, but they have the characteristics of property rights. This is the same as the theory of “materialization of claims”, which is contrary to the theory of dichotomy of property and debt. Therefore, if we take the “materialization of claims” of leasing rights as a reference, we can analyze the properties of rights related to network accounts and interpret some real problems with the conclusion.